2013
DOI: 10.1002/asi.22915
|View full text |Cite
|
Sign up to set email alerts
|

Reducing subject tree browsing complexity

Abstract: Many large digital collections are currently organized by subject; although useful, these information organization structures are large and complex and thus difficult to browse. Current online tools and visualization prototypes show small, localized subsets and do not provide the ability to explore the predominant patterns of the overall subject structure. This study describes subject tree modifications that facilitate browsing for documents by capitalizing on the highly uneven distribution of real‐world colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…This fact greatly difficult its representation in a way it is useful for an end-user browsing through it; not only due to screen limitations but also due to the user capability to avoid getting lost while trying to navigate through vast amounts of terms. Approaches like the one described by Julien et al (2013) aim to facilitate browsing for documents by capitalizing on the highly uneven distribution of real-world collections by reducing the subject tree complexity. Having information about the "distance degree" could support the decision on how to show or hide certain terms.…”
Section: Search Tacticsmentioning
confidence: 99%
“…This fact greatly difficult its representation in a way it is useful for an end-user browsing through it; not only due to screen limitations but also due to the user capability to avoid getting lost while trying to navigate through vast amounts of terms. Approaches like the one described by Julien et al (2013) aim to facilitate browsing for documents by capitalizing on the highly uneven distribution of real-world collections by reducing the subject tree complexity. Having information about the "distance degree" could support the decision on how to show or hide certain terms.…”
Section: Search Tacticsmentioning
confidence: 99%
“…The process extracts the LCSHs assigned to the bibliographic collection, which are matched to an authority record to place each bibliographic record in the LCSH hierarchy. Some researchers have developed algorithms to modify large topic structures that can overwhelm users; our LCSH hierarchy was simplified using the automated process described in Julien et al (2013). The approach opportunistically prunes a topic tree based on the expected power law distribution of topic assignments to the collection, which are common in organized information (Julien et al, 2012).…”
Section: Making a Usable Lcsh Hierarchymentioning
confidence: 99%
“…The approach opportunistically prunes a topic tree based on the expected power law distribution of topic assignments to the collection, which are common in organized information (Julien et al, 2012). Capitalizing on this trend, Julien et al (2013) reduce the size and depth of a collection's subject tree by pruning the subjects that are not representative of a collection, which was applied to our LCSH hierarchy. The implemented LCSH hierarchy contains 8,760 unique topics whose multiple inheritance duplicates produce a tree containing 578,449 topics.…”
Section: Making a Usable Lcsh Hierarchymentioning
confidence: 99%
“…This especially concerns users who are not familiar with the knowledge domains covered by the collection. Julien, Tirilly, Dinneen, and Guastavino (2013) showed that the size of the Medical Subject Heading (MeSH) hierarchy could be significantly reduced while still providing access to the vast majority of the collection. For computational efficiency, they used an estimation of the number of accessible documents offered by each subject term.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple subject assignment per document is described as a distinctive characteristic of document collections organized using a subject hierarchy as compared with digital file folder organization. The work of Julien et al (2013) is a novel line of research that aims to facilitate browsing for documents in large and complex subject hierarchies. Finally, the current study is shown to be an alternative method of indicating the subjects that can be pruned with minimal effect on collection access.…”
Section: Introductionmentioning
confidence: 99%